Atypical antipsychotic Lumateperone Beyond Schizophrenia: Seeking clarity in a time of Uncertainty - Mohamed, Wael (My University, 2022)
Lumateperone (ITI-007) is a serotonin 5HT2A tosylate salt with high affinity for dopamine D2 and D1 receptors and the serotonin transporter. It is unusual in that it controls serotonin, dopamine, and glutamate neurotransmission concurrently, all of which have been implicated in severe mental illness. Consider it a multi-targeted ligand and multifunctional modulator of the serotoninergic system with possible precognitive, antipsychotic, antidepressant, and anxiolytic properties. While lumateperone has been explored as a new agent for schizophrenia therapy, it also provides a unique therapeutic option for a range of other psychiatric and neurological diseases, including behavioural signs of dementia or Alzheimer's disease, sleep problems, and bipolar depression. Additionally, it had a better safety profile than placebo, with no significant extrapyramidal side effects, hyperprolactinemia, or changes in cardiometabolic or endocrine characteristics. Additional study is needed to validate and analyse lumateperone's effectiveness, as well as to identify prospective therapeutic targets. This article gives a comprehensive overview of the most notable results and potential future applications of this chemical in personalised medicine, particularly for neurodegenerative diseases.
Keywords: AD; Antipsychotic; Lumateperone; Schixophrenia